Organ donation awareness and attitude among Riyadh City Residents, Saudi Arabia - Aws Almufleh; Rasha Althebaity; Ali S Alamri; Nada A Al-Rashed; Eman H Alshehri; Lina Albalawi; Reem Alameer; Eman Hajr; Ismail A Raslan; Faisal A Alsaif (Wolters Kluwer Medknow Publications, 2018)
Introduction: Organ donation is widely contentious among the Saudi population though remains largely understudied. In the aim to understand the public perception of organ donation, willingness to donate, and the reasons for donation refusal, we carried out this study. Methodology: A cross-sectional questionnaire-based study was conducted on a stratified-by-region random sample of 2596 Saudi residents in Riyadh area between 15 and 70 years of age in March 2010. The main outcomes were rates of organ donation awareness, willingness to donate, and awareness of Islamic opinion permitting organ donation. Secondary exploratory analysis was performed to determine reasons for organ donation refusal. Results: Seventy-six percentage of the sample had some background knowledge of organ donation; however, 41% were unwilling to donate their organs, with only 30.1% of our sample having had a prior knowledge about Islamic opinion about organ donation. Overall, of those who had background knowledge of organ donation, 79.5% thought that organ donation was important or very important. Respondents who are women, older, more educated, and in higher income group were more likely to be aware of organ donation (P < 0.05) and those younger than 35 years old were more likely to be unaware of the Islamic opinion (P < 0.001). The most cited reasons for donation refusal included the desire to be buried with complete parts (43.8%) (i.e., not disfigured), having an incomplete idea about brain death (24%), and because they thought that it was forbidden in Islam (15.1%). Conclusion: The level of organ donation awareness was comparatively high, but knowledge of the Islamic views of organ donation lacked among high portion of our sample, which partially explains the high organ donation refusal rate. There remains a large need to promote public awareness about the importance of organ donation and to clear the confusion of the Islamic view.